2017
DOI: 10.35808/ersj/652
|View full text |Cite
|
Sign up to set email alerts
|

Financial Performance towards Value of Firms in Basic and Chemicals Industry

Abstract: This research aims to empirically prove the significant influences of financial performance towards value of firm. This research chose the population in basic and chemicals industry during the period of 2009-2014. Through purposive sampling and panel data, this research had 60 observations which was obtained through each firm. This research adopted quantitative research with random effect model, which used some analysis methods of descriptive analysis, classical assumption, multiple regression analysis and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
3
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 11 publications
1
15
3
7
Order By: Relevance
“…The results of this study are consistent with the research conducted by Karaca and Savsar (2012) and Ayuba et al (2019). Meanwhile, this research is not in line with the studies undertaken by ; Marlina (2013); Mantari and Nuryasman (2017); Purwanto and Agustin (2017) and Hutabarat, Fitrawaty and Nugrahadi (2018), which suggest that profitability has a significant effect on firm value.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…The results of this study are consistent with the research conducted by Karaca and Savsar (2012) and Ayuba et al (2019). Meanwhile, this research is not in line with the studies undertaken by ; Marlina (2013); Mantari and Nuryasman (2017); Purwanto and Agustin (2017) and Hutabarat, Fitrawaty and Nugrahadi (2018), which suggest that profitability has a significant effect on firm value.…”
Section: Resultscontrasting
confidence: 86%
“…The opportunity for shareholders to get a share of the profits (dividends) will be higher, although, unfortunately, the results of this study did not prove it. Signaling theory that describes the urge of the firm to provide reliable financial information to investors and creditors since there is the asymmetry of information (Purwanto & Agustin, 2017) was not proven either. It illustrates that the signaling theory is probably not able to work well on this research model.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study are not in accordance with the trade off theory, which states that the use of debt will increase the firm value. This study also does not support the research of Chen and Chen (2011), Manurung et al (2014), and Purwanto and Agustin (2017), which found a negative effect of the capital structure (CS) on the firm value (PV). The results of this study are also inconsistent with research from Data (2018), and Hutabarat (2018), which found a positive effect of the capital structure (CS) on the firm value (PBV).…”
Section: Effect Of the Capital Structure (Cs) On The Firm Valuecontrasting
confidence: 99%
“…The findings therefore support the studies conducted by Luthfiah and Suherman (2018) studied the effects of financial performance toward firm value of listed manufacturing companies in Indonesia stock exchange for a time frame of 5years (2012-2016) using panel data analysis with Fixed Effect Model approach and found that return on asset as a measure of financial performance have a positive and significant at 5%level of significance with or without a control variable. In the same vein; Purwanto and Agustin (2017) in their research on Financial Performance towards Value of Firms in Basic and Chemicals Industry showed that the five independent variables used as proxy for financial performance; The study aimed to empirically prove the significant influences of financial performance towards value of firm. The findings indicate that ROA had significant influences towards Price-to-Book Value of the firms which influences firm value.…”
Section: Interpretation and Discussion Of Findingsmentioning
confidence: 99%
“…A firms' competitiveness is also one factor that can affect firm value (Ansari & Raisi, 2016). Further, sustainable growth and firm's financing also influence value of a firm (Purwanto & Agustin, 2017;Riasi, 2015;Riasi & Pourmiri, 2016).…”
Section: Introductionmentioning
confidence: 99%